Patch-based techniques in medical imaging : Second International Workshop, Patch-MI 2016, held in conjunction with MICCAI 2016, Athens, Greece, October 17, 2016 : proceedings /: Second International Workshop, Patch-MI 2016, held in conjunction with MICCAI 2016, Athens, Greece, October 17, 2016 : proceedings. ([2016]) - Unknown
No abstract available